2012
DOI: 10.1126/science.1220522
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Ordered Carbon Clusters: A Crystalline Material with Amorphous Building Blocks

Abstract: Amorphous Crystals One usually thinks of a crystal as containing atoms, molecules, or other ordered units arranged in a periodic fashion to make a larger structure. L. Wang et al. (p. 825 ; see the Perspective by D. Wang and Fernandez-Martinez ) compressed a solvate of xylene in C 60 (fulleren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
139
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(147 citation statements)
references
References 30 publications
(94 reference statements)
7
139
0
1
Order By: Relevance
“…Wang et al [422] showed that C60 molecules from a crystalline solvated fullerene phase undergo an order-to-disorder transition under HP but keep their translational symmetry (Fig. 22).…”
Section: The Ordering State In Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [422] showed that C60 molecules from a crystalline solvated fullerene phase undergo an order-to-disorder transition under HP but keep their translational symmetry (Fig. 22).…”
Section: The Ordering State In Materialsmentioning
confidence: 99%
“…The HP form has a distorted Mcarbon structure [661] and is super hard, capable of indenting cubic-diamond single crystals. Similarly, compressing fullerenes causes crushed C60 cages, forming superhard forms of carbon that are quenchable to ambient pressure [422,662]. Individual C60 molecules are estimated to have an extremely high elastic modulus of 800-900 GPa [663].…”
Section: Superhard Materialsmentioning
confidence: 99%
“…Above 20 GPa, the pressure dependence of the H g (7) mode exhibits a transition and its frequency becomes almost pressure independent, which is consistent with the low compressibility of the phase formed as determined by X-ray diffraction (XRD) measurements. [15] It is worth noting that when a 514 nm laser was used for excitation the H g (8) mode became dominant above 20 GPa, instead of the H g (7) mode which dominated when the 830 nm laser was used.…”
mentioning
confidence: 99%
“…[12][13][14] Recently, Wang et al reported that compression of solvated fullerenes (C 60 /m-xylene) produces a carbon phase composed of ordered amorphous carbon clusters (OACC). [15] Such formed OACC with a long range periodic structure is challenging the categorization of solid-state materials (including crystalline, amorphous, and quasicrystalline phases). Moreover, this phase exhibits very high hardness and can indent diamond anvils at high pressure.…”
mentioning
confidence: 99%
See 1 more Smart Citation